1996
DOI: 10.1073/pnas.93.7.3043
|View full text |Cite
|
Sign up to set email alerts
|

Chronic stress alters the immune response to influenza virus vaccine in older adults.

Abstract: To

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
408
3
13

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 704 publications
(442 citation statements)
references
References 29 publications
18
408
3
13
Order By: Relevance
“…We also found that both the humoral and virus-specific cellular immune response to inoculation of an influenza virus vaccine was significantly down-regulated in caregivers as compared to control subjects (38). Caregivers were less likely to show a four-fold increase in antibody titers four weeks after vaccination; they had lower levels of in vitro stimulated IL-113; and their PBLs produced lower levels of interleukin-2 (IL-2) in response to vaccine (antigen) stimulation.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…We also found that both the humoral and virus-specific cellular immune response to inoculation of an influenza virus vaccine was significantly down-regulated in caregivers as compared to control subjects (38). Caregivers were less likely to show a four-fold increase in antibody titers four weeks after vaccination; they had lower levels of in vitro stimulated IL-113; and their PBLs produced lower levels of interleukin-2 (IL-2) in response to vaccine (antigen) stimulation.…”
Section: Discussionmentioning
confidence: 66%
“…Adults who show poorer responses to vaccines and other antigenic challenges also experience higher rates of clinical illness, including influenza virus infections (39,40). Thus, these vaccine data suggest that caregivers are more vulnerable than their age-peers to influenza and, potentially, to other infectious agents (38)(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Russo and colleagues also report caregivers to have greater prevalence of psychiatric disorders than demographically matched non-caregivers (16). Regarding health outcomes, caregivers have been found to have increased inflammation (17)and compromised immune functioning (18)relative to non-caregivers. Further, caregiving status appears to be associated with greater concentrations of stress hormones and antibodies (19), and male caregivers appear at greater risk for coronary heart disease relative to male non-caregivers(20).…”
Section: Objectivementioning
confidence: 99%
“…An early study found no relationship between life change stress or mood state and antibody response to influenza vaccination [43]. More recently, a study by Kiecolt-Glaser and colleagues [44] used the caregiver-control model in which spousal caregivers were compared to agematched controls. Caring for an elderly spouse is acknowledged as being arduous and prolonged [45] and, therefore, it is possible to use this model to assess the effects of a severe, chronic stressor on response to influenza vaccination.…”
Section: Thymus-dependent Vaccinationsmentioning
confidence: 99%